GnRH Antagonist Protocol With Cessation of Cetrorelix on Trigger Day Improves Embryological Outcomes for Patients With Sufficient Ovarian Reserve - Xu, Huihui; Zhao, Shen; Gao, Xinxing; Wu, Xian; Xia, Lan; Zhang, Dan; Li, Jian; Zhang, Aijun; Xu, Bufang (Frontiers in Endocrinology, 2021)
Objective To evaluate the efficiency and validity of cessation of cetrorelix on trigger day during gonadotropin releasing hormone antagonist (GnRH-ant)-controlled ovarian stimulation of in vitro fertilization (IVF) cycles. Methods In this retrospective study, a total of 1271 patients undergoing initial IVF cycles following the GnRH-ant protocol were enrolled; 832 patients received cetrorelix on trigger day (Group A) and 439 patients ceased cetrorelix on trigger day (Group B). We compared demographic characteristics, embryological and clinical outcomes between the two groups. A Poisson regression model was used to identify factors that significantly affected embryological outcomes. Patients were further divided into subgroups according to anti-Mullerian hormone (AMH) and age, to assess associations between ceasing cetrorelix on trigger day and embryological outcomes. Results There was a significant improvement on embryological outcomes in patients who ceased cetrorelix on trigger day, and there were no significant differences in clinical outcomes or preovulation rates between the two groups. Furthermore, for patients with 1.1 ≤ AMH ≤ 4.7 ng/ml, all embryological outcomes were significantly higher in Group B compared with Group A. For patients with AMH > 4.7 ng/ml, the number of oocytes retrieved, fertilization rate (2PN) of IVF cycles and proportion of day 3 good quality embryos were all significantly higher in Group B. For patients with age < 35 years, all the embryological outcomes, besides the number of available embryos, were significantly higher in Group B than in Group A. There were no differences in embryological outcomes between the two groups when patients were stratified based on age > 35 years or AMH < 1.1 ng/ml. Conclusion GnRH-ant protocol with cessation of cetrorelix on trigger day improved embryological outcomes for young patients or patients with sufficient ovarian reserve, and was effective at preventing preovulation.